2021
DOI: 10.3126/ajms.v12i6.33792
|View full text |Cite
|
Sign up to set email alerts
|

Approximate composition analysis and nutritive values of different varieties of edible seeds

Abstract: Background: The Dietary Guidelines for Americans (DGA) 2015-2020 supports that healthy eating patterns should include a variety of vegetables from all five of the following vegetable subgroups: dark green, red and orange, legumes, starchy, and others. Aims and Objective: To determine the approximate composition and nutritive values of edible portions of different varieties of popular seeds and to identify the heavy metals contents of these seeds. Materials and Methods: Five different seeds were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…The seed ash value of 7.38±0.05% was higher compared to values of 5.92±0.81% (Ike et al, 2020) and 3.8% (Habib et al, 2015) obtained by other researchers for C. pepo L. and C. maxima L., respectively. The pumpkin seed ash content was also higher compared to the value of 3.66±0.00% reported in previous studies (Saad et al, 2021) and 2.00±0.11 to 2.17±0.05% (Shibli et al, 2019) for H. annuus and various cultivars of A. hypogaea, respectively. The high amount of ash content denotes that Cucurbita seeds have high concentration of minerals that could assist in speeding up metabolic processes, growth and development improvement (Jacob et al, 2015).…”
Section: Nutritional Composition Of C Maxima Seed Flourcontrasting
confidence: 59%
See 4 more Smart Citations
“…The seed ash value of 7.38±0.05% was higher compared to values of 5.92±0.81% (Ike et al, 2020) and 3.8% (Habib et al, 2015) obtained by other researchers for C. pepo L. and C. maxima L., respectively. The pumpkin seed ash content was also higher compared to the value of 3.66±0.00% reported in previous studies (Saad et al, 2021) and 2.00±0.11 to 2.17±0.05% (Shibli et al, 2019) for H. annuus and various cultivars of A. hypogaea, respectively. The high amount of ash content denotes that Cucurbita seeds have high concentration of minerals that could assist in speeding up metabolic processes, growth and development improvement (Jacob et al, 2015).…”
Section: Nutritional Composition Of C Maxima Seed Flourcontrasting
confidence: 59%
“…The high amount of ash content denotes that Cucurbita seeds have high concentration of minerals that could assist in speeding up metabolic processes, growth and development improvement (Jacob et al, 2015). The crude fat content of 46.39±0.06% was higher compared to values of 36.7% (Habib et al, 2015) and 33.12±2.20 (Ike et al, 2020) for C. maxima L. and C. pepo L. but was comparable to 47.99±0.01% for pumpkin seed flour reported in Libya (Saad et al, 2021). Other authors have previously reported crude fat values of 49.80±3.53% (Shibli et al, 2019) for raw A. hypogaea and 50.80±0.01 and 48.68±2.82% for H. annuus seeds (Saad et al, 2021) in studies conducted in Pakistan and Libya, respectively which were comparable to the pumpkin seed value from this study.…”
Section: Nutritional Composition Of C Maxima Seed Flourmentioning
confidence: 45%
See 3 more Smart Citations